Effects of neuromuscular electrical stimulation, laser therapy and LED therapy on the masticatory system and the impact on sleep variables in cerebral palsy patients: a randomized, five arms clinical trial - Giannasi, Lilian Chrystiane [UNESP]; Matsui, Miriam Yumi [UNESP]; de Freitas Batista, Sandra Regina [UNESP]; Hardt, Camila Teixeira [UNESP]; Gomes, Carla Paes [UNESP]; Oliveira Amorim, Jose Benedito [UNESP]; Aguiar, Isabella de Carvalho; Collange, Luanda; dos Santos, Israel dos Reis; Dias, Ismael Souza; de Oliveira, Claudia Santos; Franco de Oliveira, Luis Vicente; et al. (Biomed Central Ltd., 2012)
Background: Few studies demonstrate effectiveness of therapies for oral rehabilitation of patients with cerebral palsy (CP), given the difficulties in chewing, swallowing and speech, besides the intellectual, sensory and social limitations. Due to upper airway obstruction, they are also vulnerable to sleep disorders. This study aims to assess the sleep variables, through polysomnography, and masticatory dynamics, using electromiography, before and after neuromuscular electrical stimulation, associated or not with low power laser (Gallium Arsenide-Aluminun, =780 nm) and LED (= 660 nm) irradiation in CP patients.Methods/design: 50 patients with CP, both gender, aged between 19 and 60 years will be enrolled in this study. The inclusion criteria are: voluntary participation, patient with hemiparesis, quadriparesis or diparetic CP, with ability to understand and respond to verbal commands. The exclusion criteria are: patients undergoing/underwent orthodontic, functional maxillary orthopedic or botulinum toxin treatment. Polysomnographic and surface electromyographic exams on masseter, temporalis and suprahyoid will be carry out in all sample. Questionnaire assessing oral characteristics will be applied. The sample will be divided into 5 treatment groups: Group 1: neuromuscular electrical stimulation; Group 2: laser therapy; Group 3: LED therapy; Group 4: neuromuscular electrical stimulation and laser therapy and Group 5: neuromuscular electrical stimulation and LED therapy. All patients will be treated during 8 consecutive weeks. After treatment, polysomnographic and electromiographic exams will be collected again.Discussion: This paper describes a five arm clinical trial assessing the examination of sleep quality and masticatory function in patients with CP under non-invasive therapies.